Arousal of cancer-associated stromal fibroblasts: Palladin-activated fibroblasts promote tumor invasion - Brentnall, Teresa A. (Landes Bioscience, 2012)
Cancer-associated fibroblasts (CAF), comprised of activated fibroblasts or myofibroblasts, are found in stroma surrounding solid tumors; these myofibroblasts promote invasion and metastasis of cancer cells. Activation of stromal fibroblasts into myofibroblasts is induced by expression of cystoskeleton protein, palladin, at early stages in tumorigenesis and increases with neoplastic progression. Expression of palladin in fibroblasts is triggered by paracrine signaling from adjacent k-ras-expressing epithelial cells. Three-dimensional co-cultures of palladin-expressing fibroblasts and pancreatic cancer cells reveals that the activated fibroblasts lead the invasion by creating tunnels through the extracellular matrix through which the cancer cells follow. Invasive tunneling occurs as a result of the development of invadopodia-like cellular protrusions in the palladin-activated fibroblasts and the addition of a wounding/inflammatory trigger. Abrogation of palladin reduces the invasive capacity of these cells. CAF also play a role in cancer resistance and immuno-privilege, making the targeting of activators of these cells of interest for oncologists.